1987
DOI: 10.1111/j.1365-2621.1987.tb05916.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermostability of Lactase (Escherichia coli) in Milk

Abstract: Denaturation of lactase in phosphate buffer was a first‐order process with a half‐life of 1.12 min at 60°C. Denaturation in milk was a biphasic first‐order process with a half‐life of 115 min at 60°C. Electrophoresis, isoelectric focusing and kinetic analysis all indicated the presence of two isozymes. The minor isozyme exhibited 9% of the total activity and was less thermostable in milk than the major isozyme. In the temperature range 53.5–60°C, the rate of denaturation of the major isozyme in milk was more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As shown in Figure 1a,b the "half-life" (time to reduced lactase activity to 50% of its original value) is about 60 min at 45°C and less than 0.5 min at 55°C. Mahoney and Wilder (1987) have reported that a representative value for the half-life of a purified lactase from Escherichia coli heated in phosphate buffer at 60°C (with added NaN 3 and MgCl 2 ) is 1.1 min. They noted that the half-life of lactase somewhat varied with the lot received from the supplier and also declined with the length of storage of the enzyme in both dry and liquid forms.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1a,b the "half-life" (time to reduced lactase activity to 50% of its original value) is about 60 min at 45°C and less than 0.5 min at 55°C. Mahoney and Wilder (1987) have reported that a representative value for the half-life of a purified lactase from Escherichia coli heated in phosphate buffer at 60°C (with added NaN 3 and MgCl 2 ) is 1.1 min. They noted that the half-life of lactase somewhat varied with the lot received from the supplier and also declined with the length of storage of the enzyme in both dry and liquid forms.…”
Section: Resultsmentioning
confidence: 99%
“…Batch C-62 min. Stabilitv lmcasurcd in milk) slowly declined during storage, as previously rep&cd (Mahoney and Wilder, 1987). Accordingly, all data in individual figures or tables wcrc obtained with a single batch of cnzymc (cxccpt whcrc stated), when the change in half-lift from the initial value was less than 10% and not significant at P~0.05.…”
Section: Methodsmentioning
confidence: 57%
“…Enzyme stability in various media was determined as described by Mahoney and Wilder (1987). All media were adjusted to pH 6.5 at the tcmpcrature of stability determination and the final enzyme concentration in the medium tested was 1 ONPG unit/ml, except where noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactase was also a little more stable in trehalose solution than in liquid buffer. Mahoney and Wilder (1987) have also reported that lactase heated at 60°C was far more stable in fluid milk than could be predicted from its behavior in liquid buffer solution. At 65°C, the heating temperature the activity of lactase in all liquid systems was almost completely lost after about 5 min (1b), although for shorter times, some stabilizing effect of milk was still apparent.…”
Section: Methodsmentioning
confidence: 96%